L'elezione delle badesse nello specchio della documentazione medievale. Un caso di studio: il monastero di San Michele in Campagna di Verona fra XII e XIII secolo - Faccin, Mara (Rivista di storia della Chiesa in Italia, 2025)
The paper examines the organization of women’s monastic communities in the Middle Ages, focusing in particular on the role of abbesses and the procedure for their election. The case study of the Benedictine monastery of San Michele in Campagna di Verona provides an opportunity to examine the power dynamics within the monastic community, its strategies for economic expansion and its relations with the outside world, including local political influences. The election of the abbess, a fundamental process for the stability of the monastic community, is examined through the electoral practice and canonical theories of the 12th and 13th centuries, with particular attention to the principle of unanimity and its evolution. Ultimately, the text highlights the importance of power relations and ritual practices associated with the election, reflecting the complexity of the role of women in medieval monasteries.